The nexus between entrepreneurial skills and generational business success - Jebolise, Chukwuka, Ernest; Nkechi, Apaokueze Tessy; Peter, Abude; Konye, Igweh Florenece (Edelweiss Applied Science and Technology, 2025)
This research paper is an empirical investigation to identify the entrepreneurial skills that can guarantee generational business success. It also seeks to ascertain the connection between entrepreneurial skills and generational business success, as well as to establish a conceptual framework for family business success. This study adopted a descriptive survey research design for this investigation through the use of questionnaires from 250 business owners, chief executives, managers, and employees of family businesses across Delta State. The results empirically identify the entrepreneurial skills required for the sustainable success of family and other businesses. The study also empirically discovered that there is a significant connection between entrepreneurial skills and the generational success of family businesses. This empirical result means that entrepreneurial skills ensure the generational business success of family businesses. For family businesses to succeed, business managers, chief executives, owners, and employees must be equipped with entrepreneurial skills. The study also found that entrepreneurial skills guarantee the sustainability of family businesses. This result has proven empirically that the only way family businesses can be sustainable and achieve generational success is through entrepreneurial skill development. The study concludes with this empirical result, which underscores the importance of entrepreneurial skills in sustainable business success in any kind of business, including family businesses. The study recommends that the human resource department of every business organization, including family businesses, must ensure that only employees with demonstrated entrepreneurial skills are hired for the sustainability of generational business success.